ELECTRIC VEHICLE ADOPTION FOR SUSTAINABLE DEVELOPMENT IN PALAKKAD: CUSTOMER AWARENESS, SATISFACTION POLICY, AND MANUFACTURING STRATEGY - Sreenidhi, T. S.; T, Kumarasamy; R , Kavipriya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research investigates the increasing usage of electric vehicles (EVs) in Palakkad, emphasizing customer awareness, satisfaction, government policy, and manufacturing strategies, with a focus on advancing sustainable development. Due to increased environmental worries and a shift towards more sustainable transportation, electric vehicles provide a green option compared to conventional gasoline-powered cars. The research is focused on evaluating how well customers understand the advantages and drawbacks of electric vehicles, their contentment with current EV options and infrastructure, and the impact of government policies on promoting EV usage. Moreover, the study investigates the production methodologies of both local and national car manufacturers, pointing out the obstacles and chances of expanding the EV manufacturing strategy to keep up with increasing demand. Data is gathered from urban and suburban areas of Palakkad to gain a thorough understanding of consumer behavior and market dynamics. This study also explores the strategies to boost EV adoption, such as rewards, financial support, and improving infrastructure such as charging points. The results seek to enhance knowledge on how EV adoption can be boosted in semi-urban areas such as Palakkad to promote environmental sustainability and economic growth in the long run.